(untitled) (MAUSAM, 1990)
Methods for agro-meteorological forecasts are mainly based on crop-weather relationship and statistical/mathematical models. Models developed from historic data make it possible to obtain the expected values fairly in advance so that appropriate action may be taken to avail of beneficial aspect of weather and minimise or avoid detrimental effect. Validity of these models under different conditions is imperative as the climatic conditions of general field may be quite different from those of experimental one. This paper discusses the work done on the above aspects.